Human neutrophil defensin-1 binding increases histidine kinase activity of SaeS in Staphylococcus aureus - Zhengfei Qi; Shuru Lin; Quanxiang Yu; Rui Ma; Kexin Zhang; Wenqi Jiang; Shurong Chen; Yilin Mai; Qingshan Bill Fu (Biochemistry and Biophysics Reports)
Human neutrophil defensin-1 (HNP-1) can specifically activate the SaeRS two-component system(TCS), which is essential for controlling virulence and immune evasion factors in Staphylococcus aureus. The reaction to HNP1 requires the transmembrane domain of SaeS (SaeS™), however the precise mechanism is yet unknown. In this work, we reconstructed the SaeS™ protein into bicelles and discovered that HNP1 can interact directly with SaeS™ using BiacoreT200, their binding significantly increases SaeS kinase activity and activated the SaeRS system subsequently. Staphylococcus aureus may exploit host-derived factors released by human immune cells to activate its two-component signal transduction system, thereby enhancing antimicrobial peptide resistance.